Management Consulting Trends in the CEE Region (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Countries of the CEE region are on their way to economic development, which is supported by foreign investments and thus technology transfer. All of them have entered the so-called investment driven growth stage by Porter during the last 3 decades. The recent challenge they have to face is the achievement of the stage of innovation-driven economic growth. The ability to create innovations presupposes knowledge-oriented domestic enterprises, as well as significant investment on R&D. The paper examines the general economic performance and innovation indicators in the 2 CEE country groups. As management consultants are directly involved in both the technology adoption process and the creation of new innovations, data of management consulting industry provide key information on the country’s innovation potential. Observing the growth paths of eight CEE countries, we can note different combinations of FDI attraction and focus on domestic corporate sector. While inflow of FDI generates immediate growth, improvement of domestic enterprises resulting stability and sovereign growth is perceptible only in the longer term.